Why is the lactation pod essential? a "Ruang Sehati" innovation pilot project for wellness tourism in Yogyakarta, Indonesia - Okinarum, Giyawati Yulilania; Vidayanti, Venny; Mulyani, Sri Hasta (Media Keperawatan Indonesia, 2024)
Yogyakarta is a popular tourist destination in Indonesia, yet lactation rooms at public facilities are difficult to access and substandard. This will certainly have an impact on breastfeeding practices for mothers who travel through their daily activities in public areas. Researchers propose using "Ruang Sehati" lactation pods as a kind of wellness tourism in Yogyakarta. This study aims to determine participants' perceptions of the lactation pod. Descriptive analytical methods were used in this study. Twenty participants were involved with this purposive sampling technique. The study showed that lactation pod innovation is essential, including maintaining privacy, sufficient breastfeeding facilities, high accessibility, and place efficiency. This innovation is also a model that can be demonstrated nationally, thereby showing a portrait of wellness tourism in the city of Yogyakarta as an ideal tourist destination for mothers and children.